Development and evaluation of nutrition knowledge measures for elementary schoolchildren (Journal of the Nutritionist-Dieticians' Association of the Philippines, 2011)
Questionnaires are the most widely used data collection methods in educational and evaluation research. This study describes the process of developing and testing questionnaires designed for use among elementary schoolchildren. Questionnaires were evaluated using difficulty index, discrimination index, distractor analyses, and internal consistency reliability tests. Upper Bicutan Elementary School participated in the study, which involved a total of 120 schoolchildren aged 9-12 years. The developed questionnaires were pilot tested and evaluated. Results showed that majority of the questions had a difficulty index of 0.3-0.7, indicative of not too easy or too difficult questions. Discrimination index revealed that most questions, particularly in Science, highly discriminated the high scorers from the low scorers. Distractor analyses showed that most of the distractors were selected, indicating that the distractors were effective. Fair to good internal consistency of the questionnaires using Cronbach's alpha ranging from 0.62 to 0.706 was obtained. In conclusion, the questionnaires may be used for the assessment of nutrition knowledge among schoolchildren. The questions may further be improved by reconstructing some of the questions and/or providing effective distractors. Further studies on the evaluation of nutrition knowledge questionnaires should be done, focusing on reliability and validity of the questionnaires. Close collaboration between content experts (nutrition) and measurement experts (educators) is essential for the the development of valid and reliable information for measurement of nutrition knowledge.